2020
DOI: 10.5194/acp-20-5547-2020
|View full text |Cite
|
Sign up to set email alerts
|

Observational analysis of the daily cycle of the planetary boundary layer in the central Amazon during a non-El Niño year and El Niño year (GoAmazon project 2014/5)

Abstract: Abstract. The Amazon biome contains more than half of the remaining tropical forests of the planet and has a strong impact on aspects of meteorology such as the planetary boundary layer (PBL). In this context, the objective of this study was to conduct observational evaluations of the daily cycle of the height of the PBL during its stable (night) and convective (day) phases from data that were measured and/or estimated using instruments such as a radiosonde, sodar, ceilometer, wind profiler, lidar and microwav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…The results found by the simulation were similar to those obtained by the ceilometer during the same time interval, with an overestimation of~50 m. For a typical day of IOP 2 (Figure 4B), during this interval, the height of the NBL was more stable at approximately 250 m. It was also observed that in the first hours of simulation (between 02 and 04 LT), the PALM model outputs underestimated (~100 m) the results found in relation to the RS and the ceilometer, and after this interval, the simulation was in agreement with the observed data. The results found for the heights of the NBL on the typical days of IOPs 1 and 2 are in agreement with the average of these IOPs, which were observed by Carneiro and Fisch [18] for the same region, verifying higher and lower fluctuations in the height of the NBL for IOPs 1 and 2, respectively. In addition, these results are similar to those reported by Neves and Fisch [26] for another site in southwestern Amazonia.…”
Section: Characteristics Of Iop 1 and Iopsupporting
confidence: 90%
See 3 more Smart Citations
“…The results found by the simulation were similar to those obtained by the ceilometer during the same time interval, with an overestimation of~50 m. For a typical day of IOP 2 (Figure 4B), during this interval, the height of the NBL was more stable at approximately 250 m. It was also observed that in the first hours of simulation (between 02 and 04 LT), the PALM model outputs underestimated (~100 m) the results found in relation to the RS and the ceilometer, and after this interval, the simulation was in agreement with the observed data. The results found for the heights of the NBL on the typical days of IOPs 1 and 2 are in agreement with the average of these IOPs, which were observed by Carneiro and Fisch [18] for the same region, verifying higher and lower fluctuations in the height of the NBL for IOPs 1 and 2, respectively. In addition, these results are similar to those reported by Neves and Fisch [26] for another site in southwestern Amazonia.…”
Section: Characteristics Of Iop 1 and Iopsupporting
confidence: 90%
“…The T3 site was located to the north of the Municipality of Manacapuru in the State of Amazonas (Figure 1), the central region of the Amazon, about 80 km from the city of Manaus. The region's altitude is approximately 50-60 m [2,18]. The data collection site, hereafter referred to as T3, is an area of pasture vegetation in a 2.5 × 2.0 km 2 clearing, 2 km north of the nearest road (AM-070) that connects Manaus with Manacapuru.…”
Section: Description Of the Experimental Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of 1.5 km is motivated by previous studies that have quantified PBL depth in nearby regions. For example, Carneiro and Fisch (2020) analysed radiosonde and remote sensing data from the GoAmazon project (Martin et al, 2016) and show that the typical minimum PBL height is 250 m and the deepest PBLs occur during daytime in the dry season and are 1.5 km deep on average. The global study by von Engeln and Teixeira (2013), based on reanalysis data, shows that PBL heights are somewhat deeper near CHC than in the Amazon but PBL heights typically range between 500 m and 1.5 km.…”
Section: Additional Diagnostics and Datamentioning
confidence: 99%